2010
DOI: 10.4103/0019-557x.70543
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of Vinyl bags in prevention of hypothermia of preterm neonates at birth

Abstract: The present study was planned to evaluate the safety and efficacy of vinyl bags in prevention of hypothermia during resuscitation at birth in very low birth weight neonates. Sixty neonates of gestational age ≤32 weeks and birth weight ≤ 1500gm were randomised to either study group, or control group. Study group neonates were put in vinyl bags up to neck and the head was covered with a cap after drying immediately following delivery and resuscitated under radiant warmer. Control group neonates were resuscitated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Our comparison of the results of the studies available in the literature with those of our study showed that body temperatures rose within the first one hour only in the study by Gathwala et al. (). It was thought that this result might have arisen from the severe hypothermia suffered by infants of lower gestational age, bodyweight, and Apgar score of infants in our study group.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our comparison of the results of the studies available in the literature with those of our study showed that body temperatures rose within the first one hour only in the study by Gathwala et al. (). It was thought that this result might have arisen from the severe hypothermia suffered by infants of lower gestational age, bodyweight, and Apgar score of infants in our study group.…”
Section: Discussionsupporting
confidence: 68%
“…() determined that the body temperature of infants placed in vinyl isolation bags (35.8 °C) was higher than that of infants who received standard care (34.9 °C) ( N = 27). The results of a study Gathwala, Singh, and Agrawal () comparing the standard care procedure with the use of vinyl isolation bags showed that the body temperatures of infants in the study group rose from 36.06 °C to 36.59 °C at the end of one hour and those of the control group rose from 35.34 °C to 36.47 °C ( N = 60). In a comparison of polyethylene caps, polyethylene occlusive wrapping, and standard care, Trevisanuto et al.…”
mentioning
confidence: 99%
“…While one recent study failed to show an effect of wrapping on hypothermia rates [64], others found that this approach effectively raised body temperature [65,66] and did so more quickly than radiant heaters [67,68], however did not reduce mortality [69]. …”
Section: Discussionmentioning
confidence: 99%
“…Transparent vinyl bags have been shown to significantly reduce heat loss in neonates, and studies have shown that they reduce evaporative loss and allow radiant heat to reach the newborn infant . However, their availability at a community level hinders their use.…”
Section: Introductionmentioning
confidence: 99%